2017
DOI: 10.1515/rela-2017-0001
|View full text |Cite
|
Sign up to set email alerts
|

The effects of explicit pronunciation instruction on the degree of perceived foreign accent in the speech of EFL learners

Abstract: This paper reports on a study that attempted to examine the effect of explicit pronunciation instruction of some English segments (individual sounds) on the degree of perceived foreign accent in EFL Arab learners’ speech. Nine Arab learners of English in an EFL (English as a foreign language) setting were assigned to two groups, experimental and control. Five utterances loaded with the taught segments were collected from both groups before and after instruction. While the experimental group received in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In the formal education setting, students are often exposed to instructors with a variety of accents and linguistic backgrounds, ranging from native speakers to non-native speakers of different proficiency levels. This diversity in accent and teaching approach, as previous research suggests, can significantly influence the learning process (Algethami 2017). Studies have shown that exposure to diverse accents can enhance students' listening skills and linguistic flexibility, preparing them for real-world language use (Burke et al 2018;Sumner 2009).…”
Section: Discussionmentioning
confidence: 97%
“…In the formal education setting, students are often exposed to instructors with a variety of accents and linguistic backgrounds, ranging from native speakers to non-native speakers of different proficiency levels. This diversity in accent and teaching approach, as previous research suggests, can significantly influence the learning process (Algethami 2017). Studies have shown that exposure to diverse accents can enhance students' listening skills and linguistic flexibility, preparing them for real-world language use (Burke et al 2018;Sumner 2009).…”
Section: Discussionmentioning
confidence: 97%
“…The comparison of results of four different groups taking part in the experiment sessions indicates that both aspects, socially constructed metalanguage, as well as critical listening, have an immediate effect on the students' performance and the initial signs of learning indicate that this approach can be an effective strategy for pronunciation instruction. However, explicit instruction did not provide any significant differences in pronunciation before or after the course in the study by Algethami (2017). Derwing et al (2007) compared two adult immigrant groups of non-native English learners comparable in education level and language proficiency but differing in mother tongue who attended a language course that concentrated on grammar and receptive communication skills.…”
Section: Pronunciation Classroom Practicesmentioning
confidence: 95%
“…Further, relative to other language skills, English pronunciation teaching in Saudi context has not been a frequently researched topic. Most of the few studies conducted on teaching pronunciation in Saudi context concentrated on the analysis of pronunciation errors produced by Saudi learners (e.g., Ahmad & Muhiburrahman, 2013;Bintuki, 2008), pronunciation difficulties and problems faced by students (e.g., Hameed & Aslam, 2015), and the effect of pronunciation instruction on learners' speech production (Algethami, 2016;Algethami, 2017). Because of the lack of research on teachers' beliefs and practices regarding pronunciation teaching in Saudi Arabia, this study is an attempt to better understand teachers' beliefs about pronunciation teaching, how pronunciation is taught, and what pronunciation training teachers have in a Saudi EFL setting.…”
Section: Introductionmentioning
confidence: 99%